Ladikli Mehmet Çelebi’nin Türkçe “Zübdetü’l-Beyan” adlı mantık eseri üzerine bir inceleme - Kızılçardak, Havva (My University, 2010)
Bu çalışmada XV. yy.da yaşamış olan Lâdikli Mehmet Çelebi’nin Zübdetü’l-beyân adlı eseri incelenmiştir. Bu eserin en önemli özelliği, tespit edilebildiği kadarıyla Türkçe yazılan ilk mantık eseri olmasıdır. Mantık ilminin düşünce tarihimizde önemli bir yeri vardır. Bu nedenle İslam medeniyetinde mantıkla ilgili hatırı sayılır bir müktesebat oluşmuştur. Bu çalışmada söz konusu risalenin mantık açısından değerlendirmesi yapılmıştır. Risalede, Ali bin Ömer el-Kazvînî el- Kâtibî’nin yazdığı er-Risaletü’ş-Şemsiyye fi kavâ‘idi’l- mantıkıyye adlı eserden mantık terimleri ve tanımları bir düzen içinde alınmış ve bunlar Türkçeye tercüme edilmiştir. Gerektiği yerde de açıklamalar yapılmıştır. Bunun dışında az da olsa başka kaynaklardan da tanımlar alınıp tercüme edilmiştir. Ancak bu tercüme, kavramların Türkçeleştirildiği bir tercüme olmamıştır. Çalışmanın son bölümünde risalenin transkripsiyon işaretleri ile Latin harflerine çevirilen haliyle beraber Arap alfabesiyle yazılan hali mevcuttur. Latin harfleriyle çevrilen metin, mantık konularına göre başlıklandırılmış ve anlam bütünlüğü olan kısımları paragraflandırılmıştır. Yapılan değerlendirmede atıflar risale yerine bu paragraflara yapılmıştır. Arap alfabesi ile yazılmış olan kısımda paragraflar konulmuş ancak başlıkları konulmamıştır. Bu çalışmanın kültürümüze ait olan değerli eserlerin tanınmasına katkı sağlayacağını umulmaktadır.

In this study, a tractate named Zübdetü’l-beyân which was written by Lâdikli Mehmet Çelebi who had lived XV. Century has been examined. As far as is identified the most remarkable attribution of the study is the first study in the logic field which is written in Turkish. Knowledge of logic has a important place in our thinking history. Because of this reason a considerable literature interested in logic has been composed in Islam civilization. In this study, the tractate in question has been evaluated in terms of logic. In tractate, logic terms and definitions has been get systematically from another study named er-Risaletü’ş-Şemsiyye fi kavâ‘idi’l-mantıkıyye written by Ali bin Ömer el-Kazvînî el- Kâtibî and these have been translated to Turkish. In case of necessity explanations has maked. Furthermore definitions from another sources, even if just a few, have been get and translated. However this translation, has not been a translation which concepts are defined in Turkish. In last chapter of the study there has been tractate’s transcription notation with text in Latin and Arabian script. The text in Latin script, has been given headings according to logic topics and separated into paragraphs. In the evaluation, references has been made to these paragraphs instead to tractate. In the text in Arabian script, there has been paragraphs but without headings. It is hoped that this study will make contribute to recognize precious studies in our culture. ABSTRACT In this study, a tractate named Zübdetü’l-beyân which was written by Lâdikli Mehmet Çelebi who had lived XV. Century has been examined. As far as is identified the most remarkable attribution of the study is the first study in the logic field which is written in Turkish. Knowledge of logic has a important place in our thinking history. Because of this reason a considerable literature interested in logic has been composed in Islam civilization. In this study, the tractate in question has been evaluated in terms of logic. In tractate, logic terms and definitions has been get systematically from another study named er-Risaletü’ş-Şemsiyye fi kavâ‘idi’l-mantıkıyye written by Ali bin Ömer el-Kazvînî el- Kâtibî and these have been translated to Turkish. In case of necessity explanations has maked. Furthermore definitions from another sources, even if just a few, have been get and translated. However this translation, has not been a translation which concepts are defined in Turkish. In last chapter of the study there has been tractate’s transcription notation with text in Latin and Arabian script. The text in Latin script, has been given headings according to logic topics and separated into paragraphs. In the evaluation, references has been made to these paragraphs instead to tractate. In the text in Arabian script, there has been paragraphs but without headings. It is hoped that this study will make contribute to recognize precious studies in our culture.
Keywords: İslam Felsefesi